Analisis Kebijakan Pendidikan Inggris Serta Perbandingan Dengan Pendidikam Di Indonesia - Hikmah Mulyanti; Lukman Lukman; Robby Setiawan; Sistya Pratiwi; Ika Kurnia Sofiani (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
discusses the analysis of education policy in England and compares it with the education situation in Indonesia. With a focus on England as a developed country, this research maps various aspects of education policy such as curriculum, funding, assessment, and follow-up after formal education. Meanwhile, education in Indonesia, as a developing country, is also experiencing significant developments in its education system. Through comparative analysis, this research evaluates the differences and similarities between the two countries, including aspects of access, quality and relevance of education. A literature review involving key references such as government reports and UNESCO publications formed the basis of this research. The results of the analysis are expected to provide insight into education policies in both countries, as well as clarify challenges and opportunities in improving the quality of education.